Empirical fluoroquinolones versus broad-spectrum beta-lactams for Gram-negative bloodstream infections in the absence of antimicrobial resistance risk factors - Majdi N. Al-Hasan; Alyssa P. Gould; Chelsea Drennan; Olivia Hill; Julie Ann Justo; Joseph Kohn; P. Brandon Bookstaver (Journal of Global Antimicrobial Resistance, 2020)
Objectives: Increasing antimicrobial resistance rates limit empirical antimicrobial treatment options for Gram-negative bloodstream infections (GN-BSI). However, antimicrobial resistance may be predicted based on patient-specific risk factors using precision medicine concepts. This retrospective, 1:2 matched cohort examined clinical outcomes in hospitalized adults without major risk factors for antimicrobial resistance receiving empirical fluoroquinolones or broad-spectrum beta-lactams (BSBL) for GN-BSI at Prisma Health-Midlands hospitals in Columbia, SC, USA from January 2010 through June 2015. Methods: Multivariable logistic regression was used to examine early treatment failure at 72–96 h from GN-BSI. Cox proportional hazards regression was used to examine 28-day mortality and hospital length of stay (HLOS). Results: Among 74 and 148 patients receiving empirical fluoroquinolones and BSBL for GN-BSI, respectively, median age was 68 years, 159 (72%) were women, and 152 (68%) had a urinary source of infection. Early treatment failure rates were comparable in fluoroquinolone and BSBL groups (27% vs. 30%, respectively, odds ratio 0.82, 95% confidence intervals [CI] 0.43–1.54, P = 0.53), as well as 28-day mortality (8.9% vs. 9.7%, respectively, hazards ratio [HR] 0.74, 95% CI 0.26–1.90, P = 0.54). Median HLOS was 6.1 days in the fluoroquinolone group and 7.1 days in the BSBL group (HR 0.73, 95% CI 0.54–0.99, P = 0.04). Transition from intravenous to oral therapy occurred sooner in the fluoroquinolone group than in the BSBL group (3.0 vs. 4.9 days, P < 0.001). Conclusions: In the absence of antimicrobial resistance risk factors, fluoroquinolones provide an additional empirical treatment option to BSBL for GN-BSI. Shorter HLOS in the fluoroquinolone group may be due to earlier transition from intravenous to oral antimicrobial therapy.